Large‐scale characteristics of reconnection diffusion regions and associated magnetopause crossings observed by MMS. Issue 5 (31st May 2017) - Fuselier, S. A.; Vines, S. K.; Burch, J. L.; Petrinec, S. M.; Trattner, K. J.; Cassak, P. A.; Chen, L.‐J.; Ergun, R. E.; Eriksson, S.; Giles, B. L.; Graham, D. B.; Khotyaintsev, Yu V.; et al.
Abstract: The Magnetospheric Multiscale (MMS) mission was designed to make observations in the very small electron diffusion region (EDR), where magnetic reconnection takes place. From a data set of over 4500 magnetopause crossings obtained in the first phase of the mission, MMS had encounters near or within 12 EDRs. These 12 events and associated magnetopause crossings are considered as a group to determine if they span the widest possible range of external and internal conditions (i.e., in the solar wind and magnetosphere). In addition, observations from MMS are used to determine if there are multiple X‐lines present and also to provide information on X‐line location relative to the spacecraft. These 12 events represent nearly the widest possible range of conditions at the dayside magnetopause. They occur over a wide range of local times and magnetic shear angles between the magnetosheath and magnetospheric magnetic fields. Most show evidence for multiple reconnection sites. Key Points: MMS X‐line events cover a wide range of external conditions Almost all X‐line events are associated with multiple X‐lines at the magnetopause Reconnection between the magnetosheath and an existing boundary layer is required for KH instability